SASI as procedure of choice and revisional bariatric surgery - Antara, Gede Eka Rusdi; Saturti, Tjokorda Istri Anom (Edelweiss Applied Science and Technology, 2025)
Obesity is a global health challenge, contributing to numerous comorbidities such as type 2 diabetes, cardiovascular diseases, and several types of cancer. While lifestyle changes, pharmacotherapy, and bariatric surgery are common treatments, bariatric surgery presents risks, including the need for revision surgeries due to complications or inadequate weight loss. One promising option for revisional bariatric surgery is the Single Anastomosis Sleeve Ileal (SASI) procedure, which has been gaining attention for its potential to offer significant weight loss with fewer complications compared to traditional revisional surgeries. The aim of this study was to evaluate the effectiveness of the SASI procedure as a potential alternative to other bariatric procedures, particularly for patients with a BMI in the range of 30-40 who have not had success with other weight-loss surgeries. This literature review synthesizes recent studies on the SASI procedure, comparing it to conventional bariatric surgeries. It highlights the procedure’s effectiveness in promoting weight loss, improving comorbidities, and maintaining relatively low complication rates. However, its role in revisional surgeries is still underexplored, showing limited success compared to its primary application. The review emphasizes the need for further research to assess the long-term outcomes of the SASI procedure, particularly regarding its ability to resolve complications, sustain weight loss, and manage postoperative issues like nutritional deficiencies. Overall, the SASI procedure shows promising potential as an alternative to traditional bariatric surgery, offering effective weight loss and safety outcomes.